SISTEM INFORMASI PENJADWALAN MENGGUNAKAN ALGORITMA GENETIKA PADA PROGRAM STUDI SASTRA INGGRIS FAKULTAS SASTRA UNIKOM - Julian Chandra Wibawa; Rofiyandi Aghitsni (Jurnal Manajemen Informatika (JAMIKA), 2012)
University lecture schedule arranging problem is a routine problem for each and every university. English Department Major Faculty of Letters Universitas Komputer Indonesia has a few courses must be scheduled. It cause very difficult to find an optimum schedule. All this time scheduling process still a manual computer use microsoft excel and microsoft word so a scheduling take a lot of time.At upper problem, then a writer purpose to make a scheduling information system with genetic algorithm. This research use a prototype system development method and use NetBeans IDE 6.8 for software with MySQL for database.After an implementation, a result is give an efective report. Writer hope this information system can help English Department Major Faculty of Letters Universitas Komputer Indonesia for rise a studying efectiveness.